Asymmetric Donor–π‐Acceptor‐Type Benzo‐Fused Aza‐BODIPYs: Facile Synthesis and Colorimetric Properties1. (25th June 2015) - Zheng, Wei; Wang, Bei‐Bei; Li, Cheng‐Hui; Zhang, Jing‐Xuan; Wan, Cheng‐Zhang; Huang, Jia‐Hao; Liu, Jian; Shen, Zhen; You, Xiao‐Zeng
Abstract Novel aza‐diisoindolylmethene and their BF2‐chelating complexes (benzo‐fused aza‐BODIPYs) were synthesized on a large scale and in a facile manner from phthalonitrile in tBuOK‐DMF solution. The unique asymmetric donor–π‐acceptor structure facilitates BN bond detachment in the presence of trifluoroacetic acid (TFA) in dichloromethane, resulting in sharp color change from red to colorless, with over 250 nm hypsochromic shift in the absorption maximum. This colorimetric process can be reversed by adding a very small amount of proton‐accepting solvents or compounds. A 1H and 11B NMR spectroscopy study and also density functional theory (DFT) calculations suggest that TFA‐induced BN bond cleavage may disrupt the whole π‐conjugation of the BODIPY molecule, resulting in significant colorimetric behavior.